1979
DOI: 10.1073/pnas.76.2.670
|View full text |Cite
|
Sign up to set email alerts
|

Structural bases of the inhibitory effects of hemoglobin F and hemoglobin A2 on the polymerization of hemoglobin S.

Abstract: We have previously found that the inhibitory effect of hemoglobin F (Hb F) on the polymerization of Hb S proceeds via the formation of asymmetrical hybrid tetramers of the type a2ts. Examination of the gelling properties of binary mixtures of Hb S and several Hb variants now shows that, among the y chain amino acid residues that differ from those of the P chain, residues y80 (EF4) and 'y87 (F3) are at least partly responsible for this inhibition. Furthermore, we find that mixing Hb A2(a2h2) with Hb S strongly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
106
0
1

Year Published

1983
1983
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(115 citation statements)
references
References 13 publications
5
106
0
1
Order By: Relevance
“…Earlier studies have shown that the inhibitory effect of HbF on the polymerization of deoxy-HbS is dependent on the formation of heterotetramers (␣ 2 ␤ S ␥) (37). A similar mechanism was proposed to explain the polymerization inhibitory effects of the naturally occurring minor hemoglobin, HbA 2 (␣ 2 ␦ 2 ) (38). Unlike the ␣ 2 ␤ A ␤ S heterotetramer, the ␣ 2 ␤ S ␥ and ␣␤ S ␦ heterotetramers are excluded from the sickle polymer, which accounts for the increased inhibitory effects of HbF and HbA 2 relative to HbA.…”
Section: Inhibition Of Hbs Polymerization By Recombinant Humanmentioning
confidence: 96%
“…Earlier studies have shown that the inhibitory effect of HbF on the polymerization of deoxy-HbS is dependent on the formation of heterotetramers (␣ 2 ␤ S ␥) (37). A similar mechanism was proposed to explain the polymerization inhibitory effects of the naturally occurring minor hemoglobin, HbA 2 (␣ 2 ␦ 2 ) (38). Unlike the ␣ 2 ␤ A ␤ S heterotetramer, the ␣ 2 ␤ S ␥ and ␣␤ S ␦ heterotetramers are excluded from the sickle polymer, which accounts for the increased inhibitory effects of HbF and HbA 2 relative to HbA.…”
Section: Inhibition Of Hbs Polymerization By Recombinant Humanmentioning
confidence: 96%
“…Key terms: Image analysis, sickle cell disease, hemoglobin F Sickle cell disease (SCD) is caused by a genetic disorder of hemoglobin ( 17), sickle hemoglobin (Hb S), which polymerizes under hypoxic conditions (12). It is known that fetal hemoglobin (Hb F) is an effective inhibitor of this polymerization (1,10, 22,27) and that Hb F level is an important determinant of the clinical course of patients with this disease. Patients with higher Hb F levels generally have a much milder clinical course, and Platt et al (25) recently reported that mean pain rate decreases as mean Hb F level increases with no threshold when hundreds of data were analyzed.…”
mentioning
confidence: 99%
“…Hb D-Ibadan (b87 [F3] Thr . Lys), which introduces a lysine residue at the b87 position, is presumed to have decreased interaction with the mutant Val residue at HbS b6 (WatsonWilliams et al 1965;Nagel et al 1979). Thus, Hb D-Ibadan inhibits HbS polymerization.…”
Section: Variants That Affect Multiple Hemoglobin Functionsmentioning
confidence: 99%
“…Several other Hb variants modulate the severity of sickle cell anemia (see also Cao and Kan 2012;Schechter and Elion 2012;Serjeant and Rodgers 2012). For example, g globin inhibits polymerization of HbS (Nagel et al 1979). This effect is attributable to differences in several amino acid residues compared with the corresponding b chain, including g80 and g87 (Adachi and Asakura 1979;Nagel et al 1979;Adachi et al 1996).…”
Section: Variants That Affect Multiple Hemoglobin Functionsmentioning
confidence: 99%
See 1 more Smart Citation